Manufacturing Industry and Coronavirus - Reepu (The journal of contemporary issues in business and government, 2021)
WHO designated coronavirus as pandemic. A virus that shook world’s economy and influenced multiple vicinities. There are multitudes who were infected, numerous recovered, some lost their lives and many are struggling. The great unwashed have adopted precautionary measures in order to break the chain. Sealings and Lockdowns are preventative methods to reduce the contacts of transmission. It’s a state where it’s like bottoms out concomitant to which manufacturing industries have been influenced. Human race is struggling to attain a better survival.